The Interaction of a Deep Western Boundary Current and the Wind-Driven Gyres as a Cause for Low-Frequency Variability - Katsman, Caroline A.; Drijfhout, Sybren S.; Dijkstra, Henk A. (2001)
Recent modeling and observational studies have indicated that the interaction of the Gulf Stream and the deep western boundary current (DWBC) in the North Atlantic may induce low-frequency (decadal timescale) variability. To understand the origin of this low-frequency variability, a line of studies is continued here addressing the stability and variability of the wind-driven circulation using techniques of dynamical systems theory. In an idealized quasigeostrophic 2-layer model setup, stationary solutions of the coupled wind-driven gyres/DWBC system are computed, using the lateral friction as control parameter. Simultaneously, their stability is assessed. When a DWBC is absent, only oscillatory instabilities with intermonthly timescales are found. However, when the strength of the DWBC is increased, the coupled 2-layer flow becomes susceptible to instabilities with interannual timescales. By computing transient flows at relatively low friction, it is found that the existence of these interannual modes induces low-frequency variability in the coupled Gulf Stream/DWBC system with a preferred interannual timescale.